V-Slot Microstrip Patch Array Antenna for 5G Applications - Muhammad Iqbal, Roslizam; Mohd Hisyam, Mohd Ariff; Mohammad Fadhil, Abas; Noor Zirwatul Ahlam, Naharuddin; Sulastri, Abdul Manap; Rahimah, Jusoh (IEEE Xplore, 2025)
The primary aim of this work is to design and analyze a microstrip patch array antenna for usage in 5G communication systems. Array antennas are extensively employed in 5G applications due to their high gain and directivity, which enhance signal strength, coverage and directional control. The microstrip patch is fabricated on FR-4 materials and configured in a 1×2 array. The antenna is engineered to comply with the frequency range of 3.4 GHz to 3.6 GHz that is regulated by the Malaysian 5G applications. The microstrip patch antenna array operates at a frequency of 3.5 GHz. The FR-4 substrate has a height of 1.6 mm and a dielectric constant of 4.7. The microstrip patch antenna array has been designed with the appropriate dimensions through theoretical analyses and computations. The principal software for modelling and simulating results is the CST Microwave Studio 2021. Gain, directivity, voltage standing wave ratio (VSWR), radiation pattern, bandwidth, and the reflection coefficient are among the critical parameters that must be analysed.